AN ANALYSIS OF ENGLISH TEXTBOOK IN THE FIRST GRADE OF JUNIOR HIGH SCHOOL - Tyas Desita Wengrum (Journal of Research on Language Education, 2020)
This research is attempted to analyze text reading from two different textbook publishers, Erlangga and Yudhistira Ghalia in the first grade of Junior High School. Those two textbooks are designed based on Curriculum 2013. The analysis is focused on the three aspects of Systemic Functional Linguistics; ideational meaning (transitivity), interpersonal meaning (mood structure), and textual meaning (theme-rheme). Those three aspects are used to analyze the contents of text reading in those two textbooks. In addition, clause complex, nominal group and lexis are used to find out the readability of those two textbooks that used by Junior High School students. These data analyzed by triangulation method. To analyze the data, the researcher used domain analysis, taxonomy analysis, componential analysis, and theme- culture analysis. The finding showed that content of reading text in Erlangga’s book is more detail in describing an object than Yudhistira Ghalia’s book. It can be concluded that Yudhistira Ghalia’s Book is more difficult and complicated for students of Junior High School than Erlangga’s book.